Exposure of Acute Gastroenteritis in Relation to Season: A Cross-Sectional Study Based on Demographic Representation of Paediatric Patients with Their Outcomes: Acute Gastroenteritis in Relation to Season: Demographic Representation of Paediatric Patients - Seema, Nighat; Saboohi, Erum; Ilyas, Adeela; Khan, Shahar Bano; Afzal, Warda; Fatima, Saiyida Kaunain (Pakistan Journal of Health Sciences, 2025)
Among children, acute gastroenteritis (viral) is a major concern for public health. In Pakistan, childhood mortality remains fourth largest, with gastrointestinal infections remaining a major cause. Objectives: To compare acute gastroenteritis and seasonal variations based on their demographic representation. Methods: After informed consent and ethical approval, this cross-sectional (prospective) research was carried out in the Paediatric Ward of Al-Tibri Medical College and Hospital, Karachi, from June 2023 to May 2024. Patients diagnosed with acute gastroenteritis were included, while those with any other diagnosis (such as intestinal obstruction, urinary tract infection, etc.) were excluded. SPSS version 23.0 was used for the analysis of data. To test significance, the chi-square test was applied at a p-value≤0.05. Results: Among 377 paediatric cases, 55% were male and 45% female, with 34% infants and 38% between 1-4 years. 63% of patients were admitted in the summer and 37% in winter, with most being admitted in May 2024 (14%) and least in the month of November 2023 (3%). The majority were discharged alive and healthy (99%). A significant association was observed in patients admitted in each month (p-value<0.001). Conclusions: This study showed that acute gastroenteritis in paediatric patients was more common among males and children aged 1–4 years, with a significantly higher number of admissions during the summer months, particularly in May 2024. Despite the seasonal surge, almost all patients recovered well, with 99% discharged alive and healthy.